Can electronic monitoring with a digital smart spacer support personalised medication adherence and inhaler technique education in patients with asthma?: Protocol of the randomised controlled OUTERSPACE trial - Job F. M. van Boven; Boudewijn H.J. Dierick; Maria Achterbosch; Sandra Been-Buck; Titia Klemmeier; Susanne J. van de Hei; Paul Hagedoorn; Huib A.M. Kerstjens; Janwillem W.H. Kocks (BMJ Open)
Introduction Medication adherence and inhaler technique in patients with asthma remain suboptimal. A digital, smart spacer may support personalised adherence and inhaler technique education. The aim of this study is to assess the feasibility of undertaking a definitive randomised controlled trial of personalised, smart spacer data-driven education and explore clinical benefits.Methods and analysis We present the design of the multicentre, randomised controlled OUtcomes following Tailored Education and Retraining: Studying Performance and AdherenCE feasibility trial of 2 months. Patients will be recruited from four Dutch general practices. At t=−1, patients with asthma ≥18 years using inhaled corticosteroids±long-acting beta-agonists±short-acting beta-agonists administered with a pressurised-metered-dose-inhaler and spacer (n=40) will use a smart spacer for 1 month. The rechargeable CE-marked smart spacer (Aerochamber Plus with Flow Vu) includes a sensor that monitors adherence and inhalation technique to prescribed dosing regimen of both maintenance and reliever inhalers. After 1 month (t=0), patients are 1:1 randomised into two groups: control group (usual care) versus intervention group (personalised education). At t=-1, t=0 and t=1 month, the Asthma Control Questionnaire (ACQ), Work Productivity and Activity Impairment (WPAI) questionnaire and Test of Adherence to Inhalers (TAI) are administered and fractional exhaled nitric oxide (FeNO) is assessed. At t=0 and t=1, spirometry is performed. At t=1, usability and satisfaction will be analysed using the System Usability Scale and interviews with patients and healthcare providers. Primary outcome is the overall feasibility of a definitive trial assessed by patient recruitment speed, participation and drop-out rate. Secondary outcomes are patient and healthcare provider satisfaction and exploratory clinical outcomes are adherence, inhaler technique, TAI score, FeNO, lung function, ACQ and WPAI.Ethics and dissemination Ethical approval was obtained from the RTPO in Leeuwarden, Netherlands (number: NL78361.099.21). Patients will provide written informed consent. Study findings will be disseminated through conferences and peer-reviewed scientific and professional journals.Trial registration number NL9637.